NUMERICAL ASSESSMENT OF A PARTIALLY STIRRED REACTOR-BASED COMBUSTION MODEL USING A HIGH-FIDELITY CFD TOOL - (:unkn) unknown (American Society of Mechanical Engineers (ASME), 2024)
In combustion systems such as those used in rotating detonation engines (RDE), turbulence chemistry interactions (TCI) play a key role. Accordingly, the main goal of this work is to assess a partially stirred reactor (PaSR) based combustion model that al...
Keywords: Combustión; Dinámica de fluidos computacional